3. Pianist Aurelia Simion - Talent, Creativity, Performance - Andriuţa Viorica (Sciendo, 2023)
Coming from a family of musicians, the descendant of a dynasty that traces its roots back to the 19th century, had Lia Oxinoit as a teacher at the pre-university cycle and Ludmila Vaverco at the Gavriil Musicescu State Conservatory from Chisinau. The artistic career of the pianist Aurelia Simion is impressive, ascending, marked by important professional successes realized in concerts and solo recitals or in collaboration with soloists, teachers, students and pupils, with participation in the Musical Olympics, in national and international competitions as an accompanist, member or president of the juries. It is particularly important to highlight the fact that Aurelia Simion, in her artistic ascent, performed on concert stages in the Romania and abroad (Ukraine, Belgium, Germany, Italy, Switzerland, France, Holland, Austria, Russia etc). Inquisitive spirit, always concerned with learning something new, she also played the harpsichord, celesta, marimbaphone and vibraphone, learned to play the portable organ with pedals, and in the moments when she had to complete the timbral color of the scores as part of the Percussion Ensemble Alternances, led by Constantin Stavrat, played claves, guiro, maracas and other small percussion instruments. Her compositional creation materialized in scores for solo piano, solo instruments with piano accompaniment, arrangements for percussion ensemble. For her academic and artistic achievements, she was awarded numerous awards, medals and diplomas of merit, honor and excellence awarded by various cultural and educational institutions.